The eye : basic sciences in practice - Forrester, John V.; Dick, Andrew D. (Andrew David); McMenamin, Paul G.; Roberts, Fiona (Pathologist); Pearlman, Eric; ClinicalKey eBooks (Edinburgh ; New York : Elsevier, 2016)
The Eye: Basic Sciences in Practice provides highly accessible, concise coverage of all the essential basic science required by today's ophthalmologists and optometrists in training. It is also essential reading for those embarking on a career in visual and ophthalmic science, as well as an invaluable, current refresher for the range of practitioners working in this area. This new fourth edition has now been fully revised and updated in line with current curricula, key research developments and clinical best practice. It succinctly incorporates the massive strides being made by genetics and f.
Anatomy of the eye and orbit -- Embryology and early development of the eye and adnexa -- Genetics -- Biochemistry and cell biology -- Physiology of vision and the visual system -- General and ocular pharmacology -- Immunology -- Microbial infections of the eye -- Pathology.
Preceded by The eye / John V. Forrester [and others]. 3rd ed. 2008.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on June 01, 2015).
Elsevier
Elsevier
Keywords: Eye; Eye -- Diseases; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Eye; Eye -- Diseases; Eye; Eye Diseases; Electronic books